PREVALENCE OF TOXOPLASMA GONDII INFECTION IN THE WORLD AND SERBIA - Blagojević, Milena; Štajner, Tijana; Marković-Denić, Ljiljana (Medicinski podmladak, 2023)
Toxoplasmosis is one of the most widespread parasitic disease caused by an obligate intracellular protozoan Toxoplasma gondii. It is estimated that one third of the human population is infected with this parasite. In immunocompetent subjects, the infection is mostly asymptomatic or is presented with flu-like symptoms, but in fetus and immunocompromised patients, infection may even be life-threatening. The prevalence of T. gondii infection varies among different countries of the world (0.5 to 87.7%) and within different regions of the same country. In Africa, the prevalence is the highest, in Asia is the lowest, while in Europe, the prevalence of toxoplasmosis ranges from low in the North to moderate in the South of the continent. The worldwide decline in the prevalence of T. gondii infection has been sustained over past few decades. In Serbia, the prevalence of toxoplasmosis tended to increase from the 1960s to the 1980s followed by a dramatic decline after that period, as in the entire Europe. The most prominent decline in the prevalence of T. gondii infection was recorded in the period from 1988 to 2007 in the population of women of reproductive age from 86% to 32.5%. The decreasing tendency of prevalence of toxoplasmosis in Serbia remains continuous even after that period of time, further confirmed by the latest results of research conducted in 2017-2018 in the population of blood donors in Belgrade (20.5% prevalence) and in the general population of Vojvodina during the 2008-2021 period (20% prevalence). Despite the encouraging epidemiological data that indicate the trend of continuous decline in the prevalence of toxoplasmosis in the world and in our country, it is still necessary to conduct additional research to indentify specific risk factors that contribute to the decrease in prevalence of T. gondii infection in the population.
Keywords: Toxoplasma gondii, prevalence, Serbia, Europe, world